Exposing the changes in work stress level among Mongolian nurses by salivary Alpha amylase test - Dondonkhuu, Otgonbaatar; Enkhbayar, Munkhtuya; Nyam, Naranbaatar; Jurmeddorj, Munkhkhand (Proceedings of the Mongolian Academy of Sciences, 2020)
When stress is part of the work environment, it is difficult to control stress, which can cause recurrent aggression, and which in turn affects an individual's health and ability to act. The relationship between workplace stressors, physical and mental health changes of the nurses have been found. A combination of high workplace demands, over-responsibility, and over-authority have been identified major sources of occupational stress among nursing staff. A total of 473 nurses from four tertiary referral hospitals of Mongolia were involved in the study. We employed a Work Stress Profile (WSP) questionnaire of Rice to figure out how nurses perceive and accept stress. The Likert scale was used in measuring the questions. Concerning physical stress factor we measured the level of α-amylase in the saliva of the nurses using the SALIVA AMYLASE MONITOR 2004, a Japanese device. Fabricated salivary amylase activity monitor consisted of three devices, the salivary transcription device, a testing-strip and an optical analyzer. Firstly, the test-strip was taken and put under the tongue for 30 seconds in the morning. Occasionally, our study was conducted during the COVID-19 pandemic quarantine period, and we could clearly see that the nurses at National Center for Infectious Diseases are working hard under the urged stressed condition.